A Comparison of All-inside and Inside-out Meniscal Repair in Elite Athletes. Issue 3 (March 2023) - Borque, Kyle A.; Laughlin, Mitzi S.; Webster, Emily; Jones, Mary; Pinheiro, Vítor Hugo; Williams, Andy
Background: The popularization of all-inside (AI) meniscal repair devices has led to a shift away from the historical gold standard of inside-out (IO) meniscal repair without comparative studies to support the change. Purpose: To compare the failure rate and time to failure of AI and IO meniscal repair performed in elite athletes. Study Design: Cohort study; Level of evidence, 3. Methods: A retrospective review was performed of all professional and national- and international-level amateur athletes who underwent meniscal repair, with a minimum of 2-year follow-up between January 2013 and September 2019. Meniscal repair was classified as AI or IO depending on the surgical technique performed. Treatment failure was defined as patients having to undergo subsequent surgery to address a persistent meniscal tear after repair. Cox proportional hazards modeling was used to determine if meniscal repair failure rates differed by the location and technique of meniscal repair. Models were controlled for known risk factors such as age, sex, sport, and concurrent cruciate ligament reconstruction. Results: A total of 192 (135 lateral and 57 medial) meniscal repairs were performed in elite athletes during the study period. Overall, 41 (21%) meniscal repairs met the criteria for failure. Medial meniscal tears repaired with the AI technique failed at a significantly higher rate (18/31 [58%]) than medial meniscal tears repaired with the IO technique (6/26 [23%]) or lateral meniscal tears repaired with the AI (9/76 [12%]) or IO (8/59 [14%]) technique ( P < .001). Cox proportional hazards modeling revealed that a medial meniscal tear repaired with the AI technique had an almost 8 times greater hazard of failure than a lateral meniscal tear repaired with the AI technique ( P < .001). At 1 year postoperatively, 8% of lateral meniscal repairs had failed (regardless of technique), while medial meniscal tears failed at a rate of 16% with the IO technique and 42% with the AI technique. By 2 years, 53% of medial meniscal tears repaired with the AI technique had failed, and by 5 years, 63% had failed. Conclusion: AI repair of medial meniscal tears led to a higher rate of failure than IO repair of medial or lateral meniscal tears in elite athletes. Medial meniscal repair failed at a higher rate than lateral meniscal repair.